Enhanced laser-induced plasma channels in air - 左言磊 魏晓峰 周凯南 曾小明 粟敬钦 焦志宏 谢娜 吴朝辉 (Chinese physics B, 2016)
Plasma is a significant medium in high-energy density physics since it can hardly be damaged. For some applications such as plasma based backward Raman amplification （BRA）, uniform high-density and large-scale plasma channels are required. In the previous experiment, the plasma transverse diameter and density are 50-200 μm and 1-2 x 10^19 cm-3, here we enhance them to 0.8 mm and 8 x 10^19 cm-3, respectively. Moreover, the gradient plasma is investigated in our experiment. A proper plasma gradient can be obtained with suitable pulse energy and delay. The experimental results are useful for plasma physics and nonlinear optics.